A Novel Adult Murine Model of Typical Enteroaggregative Escherichia coli Infection Reveals Microbiota Dysbiosis, Mucus Secretion, and AAF/II-Mediated Expression and Localization of β-Catenin and Expression of MUC1 in Ileum - Moran-Garcia, Nadia; Lopez-Saucedo, Catalina; Becerra, Adriana; Meza-Segura, Mario; Hernandez-Cazares, Felipe; Guerrero-Baez, Jair; Galindo-Gómez, Silvia; Tsutsumi, Víctor; Schnoor, Michael; Méndez-Tenorio, Alfonso; Nataro, James P.; Estrada-Garcia, Teresa (Frontiers in Cellular and Infection Microbiology, 2022)
Typical Enteroaggregative E. coli (tEAEC) is a diarrheagenic E. coli pathotype associated with paediatric and traveller’s diarrhoea. Even without diarrhoea, EAEC infections in children also lead to increased gut inflammation and growth shortfalls. EAEC strain’s defining phenotype is the aggregative adherence pattern on epithelial cells attributable to the aggregative adherence fimbriae (AAF). EAEC only causes diarrhoea in humans; therefore, not much is known of the exact intestinal region of infection and damage, or its interactions with intestinal enterocytes in vivo and in situ. Aims: to develop a new tEAEC mouse model of infection, characterize the microbiota of infected mice, evaluate in situ the expression of host adherence and surface molecules triggering EAEC infection, and the role of the EAEC AAF-II fimbria in adherence. Six-week-old C57BL/6 mice, without previous antibiotic treatment, were orally challenged with EAEC 042 strain or EAEC 042 AAF-II mutant (ΔAAF/II) strain, or DAEC-MXR strain (diffusely-adherent E. coli clinical isolate), and with saline solution (control group). Paraffin sections of colon and ileum were stained with haematoxylin/eosin and Periodic Acid-Schiff. ZO-1, β-catenin, MUC1, and bacteria were analysed by immunofluorescence. EAEC-infected mice, in comparison with DAEC-MXR-infected and control mice, significantly lost weight during the first 3 days. After 7 days post-infection, mucus production was increased in the colon and ileum, ZO-1localisation remained unaltered and morphological alterations were more pronounced in the ileum, since increased expression and apical localisation of β-catenin in ileal enterocytes was observed. EAEC-infected mice developed dysbiosis 21 days post-infection. At 4 days post-infection, EAEC strain 042 formed a biofilm on ileal villi and increased the expression and apical localisation of β-catenin in ileal enterocytes, effects not seen in animals infected with the 042 ΔAAF/II strain. At 3-days post-infection, MUC1 expression on ileal enterocytes was mainly detectable among infected mice and colocalised with 042 strains on the enterocyte surface. We developed a novel mouse model of EAEC infection, which mimics human infection, not illness, revealing that EAEC 042 exerts its pathogenic effects in the mouse ileum and causes dysbiosis. This model is a unique tool to unveil early molecular mechanisms of EAEC infection in vivo and in situ.